Life and Death of Human Vascular Endothelial Cells by Stimulation with Free Fatty Acids Through Death Receptors - Zhan, X.-R.; Mu, Y.-M.; Pan, C.-Y; Xiao, Y.-J.; Lu, Z.-Q.; Liu, F.-H.; Li, X.-Y.; Yu, J.-J. (Hormone and Metabolic Research, 2015)
Diabetic individuals may have elevated levels of serum free fatty acids and may exhibit injury to the vascular endothelial cells. This study was undertaken to determine the relationship between various free fatty acids (FFAs) and vascular endothelial cell injury and the molecular mechanisms linking FFA-induced vascular endothelial cells injury or protection. We observed the survival of HUVECs exposed to different FFAs, and our results revealed that the effects of various FFAs on the cell survival of HUVECs were significantly different. Palmitic acid (PA) markedly decreased the HUVEC survival rate in a time- and dose-dependent manner, but arachidonic acid (AA) significantly increased the cell survival rate and could partially prevent cellular apoptosis induced by PA. Interestingly, PA and AA could activate the same target receptor, TNF-R1. PA induced the apoptosis of HUVECs by initiating the death pathway (TNF-R1/TRADD/caspases 8 pathway), whereas AA enhanced cell survival to protect vascular endothelial cells by activating the survival pathway (TNF-R1/RIP/NF-κB 50/NF-κB 65).
Keywords: free fatty acids; human umbilical vein endothelial cells; TNF-R1; nuclear factor-kappa B; signaling pathways; arachidonic acid